Recent Bacteriological Trends and Emerging Antimicrobial Resistance among Hospitalized Patients in a Tertiary Care Center, Central India - Ankita Dixit; Balvir Singh; Priyanka Chaubey; Ramesh Prasad Agrawal (Journal of Pharmacy and Bioallied Sciences)
Background: Emergence of antimicrobial resistance (AMR) is a major health concern worldwide. Knowledge about common hospital organisms and their antibiograms play a crucial role in minimized mortality caused by multidrug resistance organisms (MDROs). Aim: This study determines the bacteriological trends and antibiotic resistance patterns of various clinical samples among hospitalized patients. Methods: Various clinical specimens were received and processed for culture and identification as per standard operating procedures (SOPs). Antimicrobial susceptibility tests (ASTs) were performed as per standard guidelines. Results: The prevalence of aerobic bacterial isolates was 31.68%. The most common bacterial isolates were Escherichia coli (E. coli), Staphylococcus aureus (S. aureus), Klebsiella species, and Pseudomonas species. The majority of isolates were MDROs. Conclusion: Regular surveillance of MDRO helps in implementing better therapeutic strategies to reduce morbidity and mortality associated with them.